Kisah Penyembelihan Putra Ibrahim Dalam Al-Qur’an dan Al-Kitab (Analisis Intertekstualis Julia Kristeva) - Ismu Hakiki; Muhamad Rouf Didi Sutriadi (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
The story of the slaughter of Abraham's son is one of the historical narratives in Semitic religions, including the Bible and Al-Qur'an. Although these narratives have similarities in both scriptures, there are also significant differences in the interpretation and emphasis of these stories. This article aims to conduct a comparative study of the story of the sacrifice of the son of Abraham in the Bible and the Koran using Julia Kristeva's intertextuality analysis with the aim of understanding the differences and similarities that exist in content, theological messages and implications in the two religions. The research method used is literature study. In this analysis, we will pay attention to differences in chronology, the characters involved, as well as the moral and theological messages expressed in the two versions of the story. The results of this study reveal significant differences in several aspects of the story of the slaughter of Abraham's son between the Koran and the Bible. One of the main differences lies in the identity of the son to be slaughtered. In the Qur'an, the son to be slaughtered is not explicitly named, while in the Bible, the son is referred to as Isaac. Apart from that, the theological emphasis and messages that appear in the two narratives also have striking differences. This study provides deeper insight into the differences and similarities in the story of the slaughter of Abraham's son in the Qur'an and the Bible. As a result of the analysis using intertextuality, it can be seen that the relationship between the narrative of this story in the Bible and the Qur'an is transformation, modification, demystification and parallel.